The Experiences of Patients Treated with Complete Removable Dentures: A Systematic Literature Review of Qualitative Research - Shamiso Chakaipa; Sarah J. Prior; Sue Pearson; Pieter J. Van Dam (MDPI AG, 2022)
Patient experience has been acknowledged as a critical dimension of healthcare quality alongside patient safety and clinical effectiveness. However, patient experiences in complete removable denture wearing have not been well established qualitatively. The purpose of this review was to synthesize qualitative studies that investigated the experiences of people wearing removable dentures in order to gain a deeper understanding of the issues and their causes. Databases of PubMed, SCOPUS, and CINAHL were searched to assess articles published in English from 2010 to 2021 globally. Qualitative studies that reported on experiences of people wearing removable dentures were included. A total of ten studies were included. People who wear dentures expressed diversified experiences (both negative and positive), including physical, social, psychological processes, and affective responses. Furthermore, experiences were related to emotions, maintenance of dentures, hygiene, access to care, and cost. Those wearing implant retained dentures reported more positive experiences than those who wear conventional complete dentures. Denture wearing experiences is a complex phenomenon involving the patient in wholeness including their environment. Healthcare professionals should be considering a holistic approach when providing denture rehabilitation. There is a need to further explore denture wearing experiences using qualitative approaches, as understanding of patient experiences can inform and provide clear directions on quality improvement initiatives and health-care policy development.